Optical Properties of Heterostructured ZnO/NiO Nanocomposites Synthesized via Facile Precipitation Process - ANANDAN, K; RAJESH, K.; GAYATHRI, K.; REXALIN DEVARAJ, ANITHA; MOHANBABU, M.; RAO, P. PRABHAKAR (Asian Journal of Chemistry, 2023)
The semiconductor zinc oxide/nickel oxide (ZnO/NiO) heterostructured nanocomposites have been successfully synthesized via facile and eco-friendly homogeneous precipitation process with ethanol and water as solvents. The prepared nanocomposites were studied by means of structural and optical characteristics by using X-ray diffraction, ultraviolet visible absorption and photoluminescence emission spectro-scopies. The peaks in the XRD pattern attributed to the hexagonal wurtzite structure of ZnO and face-centered cubic structure of NiO, as a result the XRD analysis further confirmed that the solvents play a powerful role in size of the crystallite of the synthesized nanocomposites. Strong UV absorption may be seen in UV-vis absorbance spectra and samples of ZnO/NiO nanocomposite materials had greater energy gap (Eg) values than those of pure NiO and ZnO materials. The synthesized materials have demonstrated high photoluminescence emission in UV-blue region in the range of 241-498 nm, it might be a valuable source for future display applications. According to the aforementioned finding, the ZnO/NiO nanocomposites showed significant promise and were a viable material for optoelectronic devices.